2022
DOI: 10.1093/ehjci/jeac129
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial strain analysis by cardiac magnetic resonance 3D feature-tracking identifies subclinical abnormalities in patients with neuromuscular disease and no overt cardiac involvement

Abstract: Aims Cardiovascular magnetic resonance (CMR) is valuable for the detection of cardiac involvement in neuromuscular diseases (NMDs). We explored the value of 2D- and 3D-left ventricular (LV) myocardial strain analysis using feature-tracking (FT)-CMR to detect subclinical cardiac involvement in NMD. Methods and results The study included retrospective analysis of 111 patients with NMD; mitochondrial cytopathies (n = 14), Friedr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“… 17 , 23 , 24 Several studies have examined the role of myocardial strain in patients with MD. 25 , 26 , 27 , 28 , 29 Of particular relevance, a recent study also applied a 3D strain analysis technique to study conventional, geometry‐dependent measures in 111 patients with a broad range of neuromuscular diseases inclusive of, but not limited, to MD. 29 Similar to our study, they observed both 3D‐GCS and 3D‐GRS are associated with the presence of replacement fibrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 17 , 23 , 24 Several studies have examined the role of myocardial strain in patients with MD. 25 , 26 , 27 , 28 , 29 Of particular relevance, a recent study also applied a 3D strain analysis technique to study conventional, geometry‐dependent measures in 111 patients with a broad range of neuromuscular diseases inclusive of, but not limited, to MD. 29 Similar to our study, they observed both 3D‐GCS and 3D‐GRS are associated with the presence of replacement fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“… 25 , 26 , 27 , 28 , 29 Of particular relevance, a recent study also applied a 3D strain analysis technique to study conventional, geometry‐dependent measures in 111 patients with a broad range of neuromuscular diseases inclusive of, but not limited, to MD. 29 Similar to our study, they observed both 3D‐GCS and 3D‐GRS are associated with the presence of replacement fibrosis. Incremental to this publication, our study provided a greater focus on MD, assessed geometry‐independent 3D strain markers, and followed up patients for MACEs to determine the predictive value of these markers.…”
Section: Discussionmentioning
confidence: 99%
“…Several observational MRI studies showed cardiac structural abnormalities among MD1 subjects, including reduced LV [47,66] or right ventricle [46] systolic function, LV hypertrophy [47] and LV non-compaction [46,67,68]; moreover, reduced values of myocardial strain, both in the longitudinal, circumferential and strain area components, have been described among MD1 patients with preserved LVEF, as per an early detection of LV contractility impairment [66,69]. (Interestingly, a non-negligible prevalence of LV LGE with a non-ischemic distribution pattern (i.e., in the mid-wall or subepicardial myocardial layers), mostly located in the inter-ventricular septum or the postero-lateral wall, has been detected in MD1 subjects, with a prevalence ranging from 12.5% [46,47] to 42% [70][71][72].…”
Section: Cardiac Magnetic Resonancementioning
confidence: 99%
“…Radial and circumferential strain can be also derived by speckle tracking echocardiography or 3-dimensional feature-tracking CMR, albeit with less-well validated cut-off values. 15 Similarly, diastolic dysfunction may be also detectable (eg, reductions in lateral/septal e′ velocities by tissue Doppler imaging) before the development of overt systolic dysfunction.…”
Section: Imaging For Dcm Diagnosis and Evaluationmentioning
confidence: 99%